Effect of freeze drying on selective bioactive compounds and physicochemical characteristics of papaya puree - Md Aslam Ali; Ahmed Redwan Haque; Mohammad Afzal Hossain; S M Kamrul Hasan (Heliyon, 2025)
Papaya (Carica papaya L.) is a delicious fruit with high nutritive value and a shorter shelf life. Freeze-drying is a well-known technique to preserve the nutritional qualities of papaya. This research aimed to investigate the effects of freeze-drying on bioactive compounds and the physicochemical properties of papaya puree. Three samples, including ‘freeze-dried papaya puree without formulation (FDP-C)’, ‘freeze-dried papaya puree formulated with composite sugars (FDP-F)’, and ‘papaya puree being neither formulated nor freeze-dried (NFD-NF)’ were prepared. The samples were analyzed to determine their phytochemicals and antioxidant activities like total phenol, flavonoid, carotenoid, ascorbic acid contents, DPPH radical scavenging, and ferric reducing antioxidant power (FRAP) assay activities. The samples were also analyzed to investigate moisture content, titratable acidity (TA), reducing sugar and total sugar contents, water absorption index (WAI), rehydration index (RI), and color attributes. FDP-C showed significantly higher phenolic (1.72 ± 0.11 mg GAE/g DM), flavonoid (1.08 ± 0.01 mg QE/g DM), carotenoid (3.75 ± 0.31 μM βCE/g DM) and ascorbic acid (4.30 ± 0.21 mg AAE/g DM), and DPPH radical scavenging (44.00 ± 0.53 mM TE/100g) and FRAP activities (359.31 ± 1.71 mM TE/100g) than that of FDP-F and NFD-NF (p < 0.05). FDF-C also showed significantly higher reducing sugar, total sugar, TA, WAI, and RI where significantly higher moisture content was obtained in NFD-NF (p < 0.05). Although statistically significant differences (p < 0.05) were observed in phytochemical content and antioxidant activity between samples, the freeze-dried papaya puree without formulation exhibits the best quality attributes regarding phytochemicals, antioxidants, chemical and sensory properties, and water indices.